1963
DOI: 10.1021/ed040p181
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of tertiary amines with nitrous acid

Abstract: The study of the history of science has made it evident that the acceptance of new theories is a complicated process. Older notions which suggested to order the universe. However, when applied to the Volume 40, Number 4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…A number of studies have confirmed the formation of Nnitrosodimethylamine from TMA and TMNO in vitro [145,146,153,174,175]. Whilst intricate mechanisms have been proposed, some involving dimethylamine as an intermediate [153], varying the reaction conditions (temperature and pH) can influence the amount of N-nitrosodimethylamine produced [153].…”
Section: N-nitrosodimethylamine Can Originate In the Body Via A Numbementioning
confidence: 98%
See 4 more Smart Citations
“…A number of studies have confirmed the formation of Nnitrosodimethylamine from TMA and TMNO in vitro [145,146,153,174,175]. Whilst intricate mechanisms have been proposed, some involving dimethylamine as an intermediate [153], varying the reaction conditions (temperature and pH) can influence the amount of N-nitrosodimethylamine produced [153].…”
Section: N-nitrosodimethylamine Can Originate In the Body Via A Numbementioning
confidence: 98%
“…A range of toxic effects have been implicated with TMA from in vivo and in vitro studies including psychosocial reactions such as depression [19,20], abnormal neurological symptoms [141], teratogenic effects [142,143], altered rRNA synthesis [144] as well as the potential to form the carcinogen N-nitrosodimethylamine [145,146] (Fig. 2).…”
Section: Potential Toxicity Of Trimethylamine and Trimethylamine-n-oxidementioning
confidence: 99%
See 3 more Smart Citations